2015
DOI: 10.3892/mco.2015.547
|View full text |Cite
|
Sign up to set email alerts
|

Association of the pri-miR-124-1 rs531564 polymorphism with cancer risk: A meta-analysis

Abstract: Abstract.Recently, several studies regarding the association between the pri-miR-124-1 rs531564 polymorphism and cancer susceptibility were explored. Owing to inconsistent results of these studies, a meta-analysis was conducted to determine the association of this polymorphism with cancer risk. Relevant studies were identified by a systematic search of PubMed, EMBASE, Web of Science and CNKI on-line databases. Odds ratios (ORs) and 95% confidence intervals (CIs) from eligible studies were pooled, and heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The findings of our meta-analysis showed that the rs531564 polymorphism was significantly associated with protection against cancer in homozygous codominant, dominant, recessive and allele inheritance model. Our findings are in agreement with the results of two meta-analyses regarding the impact of miR-124-1 rs531564 variant on cancer risk (Fang et al, 2015[ 7 ]; Li et al, 2015[ 16 ]). The meta-analysis performed by Li et al (2015[ 16 ]) enrolled 4 case-control studies and the findings revealed that rs531564 polymorphism significantly reduced cancer risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of our meta-analysis showed that the rs531564 polymorphism was significantly associated with protection against cancer in homozygous codominant, dominant, recessive and allele inheritance model. Our findings are in agreement with the results of two meta-analyses regarding the impact of miR-124-1 rs531564 variant on cancer risk (Fang et al, 2015[ 7 ]; Li et al, 2015[ 16 ]). The meta-analysis performed by Li et al (2015[ 16 ]) enrolled 4 case-control studies and the findings revealed that rs531564 polymorphism significantly reduced cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…The meta-analysis performed by Li et al (2015[ 16 ]) enrolled 4 case-control studies and the findings revealed that rs531564 polymorphism significantly reduced cancer risk. The other study conducted by Fang et al (2015[ 7 ]) with 5 case-control studies also showed that the pri-miR1241 rs531564 polymorphism significantly reduced cancer risk.…”
Section: Discussionmentioning
confidence: 86%
“…In two independent case-control studies from Xuzhou population (577 CRC patients and 690 healthy controls) and Bengbu population (323 CRC cases and 420 healthy subjects), we found that pri-miR-124 rs531564 polymorphism was significantly associated with the decreased risk of CRC, which is similar to the results of the recent meta-analysis 21 . Analysis based on bioinformatics and gene expression showed that the G allele in the rs531564 polymorphism changed the formation of a ring-shaped structure in miR-124, which was beneficial to the increase of the amount of mature miR-124 11 .…”
Section: Discussionsupporting
confidence: 87%
“…The functional rs531564 polymorphisms in pri-miR-124 may affect the mature miR-124 amount or function [20]. Previous studies stated that pri-miR-124 rs531564 polymorphism was associated with decreased risk of cancer including cervical cancer [21], esophageal squamous cell carcinoma [22], and CRC [23]. As an example, Gao et al suggested that pri-miR-124 rs531564 polymorphism contributes to the decreased risk of CRC, poor differentiation, and lymph node metastasis in the Chinese population, possibly by affecting miR-124 expression [23].…”
Section: Discussionmentioning
confidence: 99%